2008
DOI: 10.1016/j.suc.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Soft Tissue Sarcomas

Abstract: Soft tissue sarcomas in children are relatively rare. Approximately 850 to 900 children and adolescents are diagnosed each year with rhabdomyosarcoma (RMS) or one of the non-RMS soft tissue sarcomas (NRSTS). Of these, 350 are cases of RMS. RMS is the most common soft tissue sarcoma in children 14 years old and younger, and NRSTS is more common in adolescents and young adults. Infants also get NRSTS, but their tumors constitute a distinctive set of histologies, including infantile fibrosarcoma and malignant hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 34 publications
4
86
2
5
Order By: Relevance
“…Soft tissue sarcomas account for 10% of all new pediatric malignancies, 50% of which are skeletal muscle-lineage rhabdomyosarcomas (RMS) (1,2). Children with high-risk RMS endure a 3-year event-free survival rate of only 20% (3), emphasizing the need to uncover the molecular underpinnings of RMS neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Soft tissue sarcomas account for 10% of all new pediatric malignancies, 50% of which are skeletal muscle-lineage rhabdomyosarcomas (RMS) (1,2). Children with high-risk RMS endure a 3-year event-free survival rate of only 20% (3), emphasizing the need to uncover the molecular underpinnings of RMS neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Los trabajos publicados en la literatura sobre sarcomas de partes blandas en población pediátrica son escasos y, en general, analizan en forma conjunta estos dos subtipos. 2,8 En nuestra serie, presentamos 29 pacientes, todos con diagnósticos de tumores de partes blandas del tipo NRMS, tratados quirúrgicamente por un mismo equipo quirúrgico. Se describió una supervivencia del 72% a los 5 años, similar a los resultados antes reportados.…”
Section: Comentariounclassified
“…Con respecto a la quimioterapia, si bien representan un factor importante para los tumores del tipo RMS, los tumores NRMS se caracterizan por presentar mayor resistencia. 2,11 Veinticinco pacientes en nuestra serie recibieron quimioterapia como tratamiento adyuvante; sin embargo, no hemos encontrado diferencias en términos de supervivencia o recurrencia local entre los pacientes tratados con radioterapia, quimioterapia o con cirugía únicamente. El tamaño tumoral (> 5 cm), así como el margen quirúrgico positivo, han sido dos factores que fueron reportados como negativos sobre los resultados oncológicos de los pacientes.…”
Section: Comentariounclassified
See 1 more Smart Citation
“…7 Rhabdomyosarocma is the commonest paediatric soft tissue sarcoma seen but was also the commonest type in a study in Niger delta region of Nigeria in both the adult and paediatric age group. 8,9 A review of soft tissue sarcoma over a 20 year period showed the peak incidence of age occurred in the third and sixth decades of life, while another study showed the mean age of presentation of soft tissue sarcoma to be 37.4±12.6 years and the age range from 18 to 85 years among adult population but with inclusion of paediatric age group in another study, the youngest patient seen was 3 years and the oldest was 73 in another study. 8 There is a slight gender predilection seen in soft tissue sarcoma in males compared to females.…”
Section: Introductionmentioning
confidence: 98%